(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Natural compound extracted from microorganism is one of the important compound used for treatment many diseases in the world ? -glucan is one of these compound that extracted from yeast Saccharomyces cerevisiae by acid alkaline method used by Biron. The glucan was analyzed by FTIR ,HPLC, molecular weight was determined and antioxidant effect of ? -glucan was tested . The result showed high compatibility between the sample of glucan and the standard by FTIR, ? -glucan showed high purity of extraction as compared with standard of glucan by using HPLC.